Preparing Emergency Physicians for Acute Disaster Response: A Review of Current Training Opportunities in the US. Issue 6 (19th September 2016) - Hansoti, Bhakti; Kellogg, Dylan S.; Aberle, Sara J.; Broccoli, Morgan C.; Feden, Jeffrey; French, Arthur; Little, Charles M.; Moore, Brooks; Sabato, Joseph; Sheets, Tara; Weinberg, R.; Elmes, Pat; et al.
Abstract: Study Objective: This study aimed to review available disaster training options for health care providers, and to provide specific recommendations for developing and delivering a disaster-response-training program for non-disaster-trained emergency physicians, residents, and trainees prior to acute deployment. Methods: A comprehensive review of the peer-reviewed and grey literature of the existing training options for health care providers was conducted to provide specific recommendations. Results: A comprehensive search of the Pubmed, Embase, Web of Science, Scopus, and Cochrane databases was performed to identify publications related to courses for disaster preparedness and response training for health care professionals. This search revealed 7, 681 unique titles, of which 53 articles were included in the full review. A total of 384 courses were found through the grey literature search, and many of these were available online for no charge and could be completed in less than six hours. The majority of courses focused on management and disaster planning; few focused on clinical care and acute response. Conclusion: There is need for a course that is targeted toward emergency physicians and trainees without formal disaster training. This course should be available online and should utilize a mix of educational modalities, including lectures, scenarios, and virtual simulations. An ideal course should focus on disaster preparedness, and the clinical and non-clinical aspects of response, with a focus on an all-hazards approach, including both terrorism-related and environmental disasters. B Hansoti, DS Kellogg, SJ Aberle, MC Broccoli, J Feden, A French, CM Little, B Moore, J Sabato Jr., T Sheets, R Weinberg, P Elmes, C Kang .Preparing emergency physicians for acute disaster response: a review of current training opportunities in the US .Prehosp Disaster Med .2016 ;31 (6 ):643 –647 .